2011
DOI: 10.3727/096504011x12935427587722
|View full text |Cite
|
Sign up to set email alerts
|

KITENIN Is Associated With Activation of AP-1 Target Genes via MAPK Cascades Signaling in Human Hepatocellular Carcinoma Progression

Abstract: KITENIN promotes cancer cell migration and invasion in vitro and cancer metastasis in mouse cancer models, including colon and head and neck cancers. The purposes of this study were to observe the effect of KITENIN on tumor cell behaviors of human hepatocellular carcinoma (HCC) cells and to evaluate its expression in human HCC tissues. To functionally characterize KITENIN in human HCC, we depleted its expression in human HCC cell lines, HepG2 and Huh7, by using small interfering RNA (siRNA). Invasion and proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…We have previously shown that expression of VANGL1 is increased with malignancy of the 21T series cells7, although a potential functional role for VANGL1/PCP pathway in this system has yet to be explored. According to recent reports, downregulation of VANGL1 expression inhibits progression of hepatocellular carcinoma cells18, and this has been shown to be associated with decreased expression of AP-1 target genes such as COX-2 and MMP319. VANGL1 has also been shown to bind to the metastasis suppressor KAI1/CD82 in the mouse colon cancer cell line CT-26, increasing invasiveness and adhesion to fibronectin in vitro and increasing tumorigenicity and metastasis in vivo20.…”
mentioning
confidence: 99%
“…We have previously shown that expression of VANGL1 is increased with malignancy of the 21T series cells7, although a potential functional role for VANGL1/PCP pathway in this system has yet to be explored. According to recent reports, downregulation of VANGL1 expression inhibits progression of hepatocellular carcinoma cells18, and this has been shown to be associated with decreased expression of AP-1 target genes such as COX-2 and MMP319. VANGL1 has also been shown to bind to the metastasis suppressor KAI1/CD82 in the mouse colon cancer cell line CT-26, increasing invasiveness and adhesion to fibronectin in vitro and increasing tumorigenicity and metastasis in vivo20.…”
mentioning
confidence: 99%
“…KITENIN participates in the dissemination of colorectal (14), head and neck squamous (15,16), gastric (17), and hepatocellular cancer cells (18). We observed a tumor-regressive effect of KITENIN siRNA when introduced intravenously in a mouse colon tumor model (19,20).…”
Section: Introductionmentioning
confidence: 72%
“…KITENIN protein expression is significantly higher in human colon (11,12), laryngeal (14), oral cavity squamous (15), gastric (16), and hepatocellular (17) cancer tissues than in corresponding normal mucosa or early-stage cancer tissues. Interaction of KITENIN with Dishevelled (Dvl)/PKCd is important in regulating colorectal cancer cell invasion via ERK/AP-1 activation (11) and expression of KITENIN is significantly associated with lymph node metastasis and poor survival of colorectal cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we identified KAI1 C-terminal interacting tetraspanin (KITENIN) as a metastasis-enhancing gene (9,10) that participates in the dissemination of colorectal (11,12), squamous (13)(14)(15), gastric (16), and hepatocellular cancer cells (17). KITENIN protein expression is significantly higher in human colon (11,12), laryngeal (14), oral cavity squamous (15), gastric (16), and hepatocellular (17) cancer tissues than in corresponding normal mucosa or early-stage cancer tissues.…”
Section: Introductionmentioning
confidence: 99%